Zika virus-like particles (VLPs): Stable cell lines and continuous perfusion processes as a new potential vaccine manufacturing platform. Issue 47 (8th November 2019) - Alvim, Renata G.F.; Itabaiana, Ivaldo; Castilho, Leda R.
Abstract: Zika virus (ZIKV) was first detected in Brazil in 2015 and then rapidly spread to more than 80 countries in Africa, Asia and the Americas. ZIKV infection was correlated with severe congenital malformations in newborns from infected mothers, as well as with Guillain-Barré syndrome in adults. Although the number of infected people has declined in the affected countries lately, the development of a vaccine for ZIKV is of great importance to avoid the future resurgence of the virus in endemic areas or the future spread to currently non-endemic regions. Among many different platforms currently under study, virus-like particles (VLPs) are a promising alternative for the development of vaccines, since tridimensional particles mimicking the virus – but lacking its genome – can be produced and present the antigen in a repetitive way, potentially eliciting robust immune responses. In this work, we demonstrated the generation of stably transfected HEK293 cells constitutively expressing Zika VLPs. Small-scale shake flask studies using a stable cell pool enriched by Fluorescence-Activated Cell Sorting (FACS) showed that daily medium exchange (intermittent perfusion) significantly enhances viable cell density and VLP production (∼4-fold) over batch cultures. Continuous perfusion in a controlled bioreactor coupled to an ATF-2 cell retention device resulted in maximum VLP titers similar to those obtained under small-scale intermittent perfusion. Our results show that the use of cell lines constitutively expressing Zika VLPs, cultured in stirred-tank perfusion bioreactors, represents a promising system for the production of a VLP-based Zika vaccine candidate.